2010
DOI: 10.1088/0022-3727/44/3/034008
|View full text |Cite
|
Sign up to set email alerts
|

Stretching-induced interconnect delamination in stretchable electronic circuits

Abstract: Abstract. Stretchable electronics offer increased design freedom of electronic products. Typically, small rigid semiconductor islands are interconnected with thin metal conductor lines on top of, or encapsulated in, a highly compliant substrate, such as a rubber material. A key requirement is large stretchability, i.e. the ability to withstand large deformations during usage without any loss of functionality. Stretching induced delamination is one of the major failure modes that determines the amount of stretc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 34 publications
1
47
0
Order By: Relevance
“…As a result, the structural dissipation due to plastic deformation of the copper film, Γ str , is directly incorporated. For the PDMS, a Neo-Hookean model with C 10 = 0.165 MPa is identified from the uniaxial data (figure A.5), similarly as is used by van der Sluis et al (2011a). Hoefnagels et al (2010) observed a fibrillation mechanism at the peel front.…”
Section: Mesoscale Characterizationmentioning
confidence: 97%
“…As a result, the structural dissipation due to plastic deformation of the copper film, Γ str , is directly incorporated. For the PDMS, a Neo-Hookean model with C 10 = 0.165 MPa is identified from the uniaxial data (figure A.5), similarly as is used by van der Sluis et al (2011a). Hoefnagels et al (2010) observed a fibrillation mechanism at the peel front.…”
Section: Mesoscale Characterizationmentioning
confidence: 97%
“…These FLDs apply to copper foils described by rigid-plastic constitutive equations (or elasto-plastic models with h/E 1). The material parameters corresponding to four hardening models (i.e., linear, Hollomon, Swift and Voce laws) have been identified using a UT experiment provided in van der Sluis et al [2011], and the relevant values of these parameters are reported in Fig. 4.…”
Section: -19mentioning
confidence: 99%
“…[64] As a proof of concept, we demonstrate that the stretchable electrode can be used to detect EMG signals and that the stretchable strain sensor can be utilized to simultaneously monitor the deformation induced by the elbow bending. [50][51][52][53][54][55][56][57][58][59][60][61] Adhesion is crucial for the long-term use of stretchable electronics, such as the detection of body-surface biosignals in electromyography (EMG) and electrocardiography (ECG), and implanted devices where the interface friction may easily induce failures of debonding. It also opens up for exploration of the advanced property-function relationships combining high adhesion and stretchability.…”
mentioning
confidence: 99%
“…[50][51][52][53][54][55][56][57][58][59][60][61] Adhesion is crucial for the long-term use of stretchable electronics, such as the detection of body-surface biosignals in electromyography (EMG) and electrocardiography (ECG), and implanted devices where the interface friction may easily induce failures of debonding. This is due to the huge difference in physical and chemical properties (e.g., Young's modulus: tens of GPa for gold while only several MPa for PDMS) between the conductive material and the elastic substrate.…”
mentioning
confidence: 99%